Factors Influencing the Risk of Internet Addiction Disorders in Adolescents in Indonesia - Maharani, Ni Komang Putri Bintang (International Journal Education and Computer Studies (IJECS), 2025)
Internet addiction represents a behavioral disturbance marked by an uncontrollable urge to access the internet, often to the extent that it disrupts daily routines and social interactions. The rapid expansion of internet access in Indonesia has made adolescents increasingly susceptible to problematic usage patterns, raising concerns about the long-term impact on their psychological and social well-being. This literature review aims to map out the underlying factors that contribute to the risk of Internet Addiction Disorder (IAD) among Indonesian adolescents. Sources were identified using the keywords “Internet Addiction Disorder” and “Kecanduan Internet” on Google Scholar and Garuda. The analysis reveals that the risk of internet addiction in adolescents is shaped by a combination of internal and external influences. Internal factors include aspects such as self-control, self-regulation, academic stress, and self-esteem. Meanwhile, external factors involve parenting style, peer environment, prosocial behavior, and participation in religious activities. The presence of low self-control and poor self-regulation often correlates with a greater tendency toward excessive internet use, especially when accompanied by high academic pressure or a lack of supportive social structures. On the other hand, positive parenting, strong social bonds, and engagement in community or religious activities appear to provide a protective buffer. Understanding these interconnected factors is essential for developing targeted prevention and intervention strategies that address both personal vulnerabilities and environmental triggers. The insights from this review may assist educators, parents, and policymakers in fostering healthier digital habits among adolescents.